2012
DOI: 10.1177/229255031202000317
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fibrin sealant on the prevention of seroma formation after postbariatric abdominoplasty

Abstract: Fibrin sealant was a useful adjunct during surgical wound closure and significantly decreased seroma formation in patients undergoing postbariatric abdominoplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 14 publications
(7 reference statements)
1
10
0
Order By: Relevance
“…In the present study, we found a signi cant decrease in the total volume of aspirated uid in the group who received brin glue compared to the control. This nding is in accordance with the results documented by other authors who used commercial brin glue in their interventions [5,[7][8][9]. However, con icting results were found by other authors, who reported inconclusive results or even harmful effects of brin glue which were explained by the presence of drains that may interfere with the maturation of the brin clot and the blockage of the lymphatic vessels [16][17][18].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, we found a signi cant decrease in the total volume of aspirated uid in the group who received brin glue compared to the control. This nding is in accordance with the results documented by other authors who used commercial brin glue in their interventions [5,[7][8][9]. However, con icting results were found by other authors, who reported inconclusive results or even harmful effects of brin glue which were explained by the presence of drains that may interfere with the maturation of the brin clot and the blockage of the lymphatic vessels [16][17][18].…”
Section: Discussionsupporting
confidence: 90%
“…Fibrin glue, light-activated brin sealant, and transdermal photopolymerized adhesive have been associated with reduction in the uid build-up post mastectomy through various studies [6][7][8][9]. Fibrin glue acts by lessening the number of disrupted lymphatics and minute vessels during axillary dissection hence resulting in lowering of seroma output [6,10] and provide hemostasis by controlling the hematomas which may delay wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…Wattin and Look [27] have suggested the use of a spray version of the glue to allow a better distribution over the entire surface, while a recent Canadian study demonstrates that the fibrin glues are a useful adjunct during surgical wound closure and significantly decrease seroma formation in patients undergoing postbariatric abdominoplasty [28].…”
Section: Discussionmentioning
confidence: 99%
“…Its role in seroma prevention has been studied with varying results in mastectomy and thyroidectomy patients. [9][10] Human fibrin glue (HFG) is formed of two components contained in separate vials; the first component is a freeze-dried concentrate of clotting proteins, mainly fibrinogen, Factor XIII and fibronectin (the sealant) and the second substance is freeze dried thrombin (the catalyst). The first component is reconstituted with an aprotinin solution that inhibits tissue fibrinolysis.…”
Section: Introductionmentioning
confidence: 99%